Optimalisasi Pendidikan Agama Islam Dalam Membentuk Karakter Islami Pada Siswa SMK Kartika Generasi Z - Defirra Alizunna, Nurhasan (Al-Makrifat: jurnal kajian Islam, 2024)
This research aims to explore and analyze the optimization of Islamic religious education that is effective in forming Islamic character in generation Z Vocational Middle School students at Kartika Grati Pasuruan Vocational School. Generation Z students, as a group that grew up in the technological era of globalization, have unique educational needs and dynamics. The research method used is a case study, by collecting data through in-depth interviews, participant observation, and document analysis. Through this approach, we can understand in depth the experiences and perceptions of generation Z students regarding the Islamic education process they receive at Kartika Grati Pasuruan Vocational School. as well as the extent to which their Islamic character developed in this context. The results of the research show that (1) the importance of strategies for optimizing Islamic education at Kartika Grati Vocational School include those based on Islamic values, technology in Islamic education, direct experience and active learning, the role of social collaboration, the effectiveness of Islamic education strategies; and continuing education in everyday life; (2) implications for the development of Islamic education at Kartika Grati Vocational School including the characteristics of generation Z students; relevance of contemporary challenges; recognition of global cultural influences; challenges and obstacles; Islamic education innovation; and the influence of the campus environment. It is hoped that the results of this research can contribute to students in general, especially Kartika Grati Vocational School, in improving and optimizing Islamic education strategies for generation Z, by focusing on important aspects of Islamic character formation. Keywords: Islamic Religious Education, Islamic Character, Generation Z